1995
DOI: 10.1007/bf02331909
|View full text |Cite
|
Sign up to set email alerts
|

The nervous system of Tricladida. I. Neuroanatomy ofProcerodes littoralis (Maricola, Procerodidae): An immunocytochemical study

Abstract: The organization of the nervous system of Procerodes littoralis (Tricladida, Maricola, Procerodidae) was studied by immunocytochemistry, using antibodies to authentic flatworm neuropeptide F (NPF) (Moniezia expansa). Compared to earlier investigations of the neuroanatomy of tricladid flatworms, the pattern of NPF immunoreactivity in Procerodes littoralis reveals differences in the following respects: 1. Shape and structure of the brain. 2. Number and composition of longitudinal nerve cords. 3. Shape of branche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…However, the present study has revealed that the brain is butterfly shaped and possesses a single, broad commissure. A recent study of Procerodes littoralis, another maricolan triclad species, gives an account of the brain structure (Reuter et al, 1995a). In P. littoralis the brain is described as "butterfly-shaped," only one brain commissure was present, and, in contrast to the spongy appearance which was reported in the brain of Dugesia spp (Bagufik and Ballester, 1978), the brain of P. littoralis was compact with peripherally-located cell bodies.…”
Section: Discussionmentioning
confidence: 96%
“…However, the present study has revealed that the brain is butterfly shaped and possesses a single, broad commissure. A recent study of Procerodes littoralis, another maricolan triclad species, gives an account of the brain structure (Reuter et al, 1995a). In P. littoralis the brain is described as "butterfly-shaped," only one brain commissure was present, and, in contrast to the spongy appearance which was reported in the brain of Dugesia spp (Bagufik and Ballester, 1978), the brain of P. littoralis was compact with peripherally-located cell bodies.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies on the CNS of freshwater planarians have described the organization of the nervous system in intact organisms (Reuter et al 1995a,b, 1996; Agata et al 1998; Tazaki et al 1999). However, little attention has been paid to how this CNS is formed during regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The primary structure of this M. expansa NPF neuropeptide displays strong sequence similarities with vertebrate neuropeptide Y (15). Subsequently, immunochemical analysis using antibodies against M. expansa NPF and against vertebrate PP, Peptide tyrosine tyrosine (PYY) and Substance P (SP) revealed the presence of immunoreactive substances in other cestodes (8285) and other flatworm classes, including turbellarians (16, 86, 87), monogeneans (8891), and trematodes (17, 9294). So far, the immunopositive material has only been identified in Arthurdendyus triangulates (16), Schistosoma mansoni and in Schistosoma japonicum (17).…”
Section: The (Long) Npf Signaling System and Its Role In Feeding And mentioning
confidence: 99%